Molluscicidal effect of Achyranthes aspera L. (Amaranthaceae) aqueous extract on adult snails of Biomphalaria pfeifferi and Lymnaea natalensis - Belayhun Mandefro; Seid Tiku Mereta; Yinebeb Tariku; Argaw Ambelu (BMC, 2017)
Abstract Background Intestinal schistosomiasis caused by Schistosoma mansoni is a wide spread disease in most parts of Ethiopian highlands. Snail control is one major strategy in schistosomiasis control. The use of molluscicidal plant products is becoming interesting due to their environmental friendliness, accessibility and easy application. This research is aimed to evaluate the molluscicidal effect of Achyranthes aspera on Biomphalaria pfeifferi and Lymnaea natalensis snails, which are of great medical and veterinary importance in Ethiopia. Methods Adult B. pfeifferi snails were exposed to the various concentrations of A. aspera aqueous leaf extract for 24, 48 and 72 h. Similarly, adult L. natalensis snails were exposed to the extract for 24 h. Mortality data were analyzed using probit regression model. Phytochemical content of the plant was analyzed using standard screening methods. Results The plant's molluscicidal effect on the two snail species was demonstrated. The 24 h LC50 and LC90 values against L. natalensis were 69.5 and 93.9 ppm respectively. In the 24, 48 and 72 h exposure of B. pfeifferi, the LC50 values were 72.4, 69.9, 64.7 ppm and the LC90 were 96.5, 93.8, 92.8 ppm, respectively. The phytochemical screening tests indicated presence of saponins. Conclusion From the findings of this study, A. aspera has a molluscicidal potential. The result provides a useful foundation for further in-depth studies to ensure its wider applicability in different water bodies and evaluate its toxic effects on non-target species.